2014
DOI: 10.1158/1055-9965.epi-13-0437-t
|View full text |Cite
|
Sign up to set email alerts
|

Genes–Environment Interactions in Obesity- and Diabetes-Associated Pancreatic Cancer: A GWAS Data Analysis

Abstract: Background Obesity and diabetes are potentially alterable risk factors for pancreatic cancer. Genetic factors that modify the associations of obesity and diabetes with pancreatic cancer have previously not been examined at the genome-wide level. Methods Using GWAS genotype and risk factor data from the Pancreatic Cancer Case Control Consortium, we conducted a discovery study of 2,028 cases and 2,109 controls to examine gene-obesity and gene-diabetes interactions in relation to pancreatic cancer risk by emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 44 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…However, whether the association between diabetes and obesity is linked to a further enhanced risk of PanCA development is not yet clear as different studies have had conflicting results [26, 27]. A number of studies have also demonstrated the association between obesity and pancreatic inflammation [2428]. Interestingly, all known risk factors for PanCA can contribute to or cause inflammation of the pancreas (pancreatitis) [16, 30].…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, whether the association between diabetes and obesity is linked to a further enhanced risk of PanCA development is not yet clear as different studies have had conflicting results [26, 27]. A number of studies have also demonstrated the association between obesity and pancreatic inflammation [2428]. Interestingly, all known risk factors for PanCA can contribute to or cause inflammation of the pancreas (pancreatitis) [16, 30].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Machine learning methods have been used for the biomarker discovery from high-throughput omics data, inferring causal relations between mutations and diseases [21] , interactions between genes and proteins [86][87][88] and relations between environmental features and cancer [89] as well as pathway and network modeling. There are two kinds of basic machine learning techniques, one is unsupervised machine learning such as hierarchical clustering, self-organizing mapping (SOM) etc.…”
Section: Machine Learningmentioning
confidence: 99%
“…Large-scale consortia have been successful in other diseases, including AMD and T2D. [29, 32, 4245] We are hopeful that when these same strategies are employed in GWAS for DR, we will begin to uncover the genetic underpinnings of this disease.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%